Safety and activity of PD-1 blockade-activated DC-CIK cells in patients with advanced solid tumors. (3rd April 2018) - Chen, Chang-Long; Pan, Qiu-Zhong; Weng, De-Sheng; Xie, Chuan-Miao; Zhao, Jing-Jing; Chen, Min-Shan; Peng, Rui-Qing; Li, Dan-Dan; Wang, Ying; Tang, Yan; Wang, Qi-Jing; Zhang, Zhi-Ling; et al.
ABSTRACT: Cytokine-induced killer (CIK) cells that are stimulated using mature dendritic cells (DCs), referred to as (DC-CIK cells) exhibit superior anti-tumor potency. Anti-programmed death-1 (PD-1) antibodies reinvigorate T cell-mediated antitumor immunity. This phase I study aimed to assess the safety and clinical activity of immunotherapy with PD-1 blockade (pembrolizumab)-activated autologous DC-CIK cells in patients with advanced solid tumors. Patients with selected types of advanced solid tumors received a single intravenous infusion of activated autologous DC-CIK cells weekly for the first month and every 2 weeks thereafter. The primary end points were safety and adverse event (AE) profiles. Antitumor responses, overall survival (OS), progression-free survival (PFS) and cytolytic activity were secondary end points. Treatment-related AEs occurred in 20/31 patients. Grade 3 or 4 toxicities, including fever and chills, were observed in two patients. All treatment-related AEs were reversible or controllable. The cytotoxicity of DC-CIK cells induced up-regulation of PD-L1 expression on autologous tumor cells. When activated using pembrolizumab ex vivo, DC-CIK cells exerted superior antitumor properties and elevated IFN-γ secretion. Objective responses (complete or partial responses) were observed in 7 of the 31patients.These responses were durable, with 6 of 7 responses lasting more than 5 months. The overall disease control rate in the patients was 64.5%. At the time of this report, the median OS and PFS were 270 and 162 days, respectively. In conclusions, treatment with pembrolizumab-activated autologous DC-CIK cells was safe and exerted encouraging antitumor activity in advanced solid tumors. A larger phase II trial is warranted.